Moenkhausia goya (Characiformes: Characidae): a new species from the upper rio Tocantins basin, Central Brazil - Deprá, Gabriel De Carvalho; Azevedo-Santos, Valter M.; Vitorino, Oscar Barroso Júnior; Dagosta, Fernando Cesar Paiva; Marinho, Manoela Maria Ferreira; Benine, Ricardo C. (Zootaxa, 2018)
A new species of Moenkhausia is described from the upper rio Tocantins basin, States of Goiás and Tocantins, Brazil. Moenkhausia goya, new species, can be distinguished from its congeners by the shape of the humeral blotch in combination with a uniform dark pigmentation covering the interradial membranes of the dorsal and anal fins. Among congeners, the new species is most similar to M. britskii Azevedo-Santos & Benine, M. grandisquamis (Müller & Troschel) and M. xinguensis Steindachner by presenting a deep body, a large, round humeral blotch and fins without discrete patches of dark pigmentation (i.e., without well-defined blotches or stripes). With the description of M. goya, the number of species endemic to the upper rio Tocantins basin (considered upstream from the mouth of the rio Paranã) is raised to 51. Of these, some are widespread in the upper rio Tocantins basin, while others seem to be restricted to one of its sub-basins.